Media intervention in post-war settings: Insights from the Epistemologies of the South - Santos, Sofia Jose; Araújo, Sara; Cravo, Teresa Almeida (Commons. Revista de Comunicación y Ciudadanía Digital, 2016)
Over the past two decades, international intervention in post-war settings has strictly followed liberal assumptions and practices. Efforts to build and shape the media in the aftermath of armed conflict are no exception. In setting the foundations for the rule of law, liberal democracy and free market, external actors have (re)defined what constitutes the mediascape – that is, the various spheres of communication within public discourse – and how to (re)construct it. Imprinted with modernity’s tenets and western assumptions about the public space, this approach has understood the mediascape narrowly as limited to traditional, established, liberal media, serving to validate particular actors and processes whilst obscuring, neglecting and shutting off global diversity. Law and technology, this paper argues, are the two main axes through which legitimation and exclusion are effected. A myopic focus on legal and technological aspects of the media reduces a rich space of local discourses, norms and practices to western-like media legislation, training and outlets, narrowing in turn the sites for addressing violence and building peace.